Rehabilitation of Sg Kembong open dumpsite using Geographic Information System: A case study / Cindy Chai - Cindy, Chai (2012)
Municipal solid waste disposal site has always posed serious environmental issues since its construction until the post closure stage. Generation of landfill gas and leachate towards the surroundings has caused various environmental and health hazards. To prevent the situation from deteriorating, landfill rehabilitation of any unsanitary disposal sites is momentous. In accordance to the Tenth Malaysia Plan (2011-2015), the government will close and rehabilitate the existing 158 unsanitary landfills by 2015 to ensure that solid waste management is well-managed in a sustainable manner. Sungai Kembong Open Dumpsite (SKOD) has been identified as one of the unsanitary landfill under the the Kajang municipality in Selangor, Malaysia. It has been urged to close down due to its leakage of leachate into the water body which has polluted the water treatment plant in Semenyih that supplies the water to millions of residents. Therefore, SKOD was chosen as a study area for the rehabilitation and safe closure process based on the guidelines published by the Ministry of Housing and Local Government of Malaysia. Given the increasing concern about the environmental and health hazard posed by the open dumpsite, it is vital to rehabilitate the closed SKOD in a systematic and technically-sound way. This research study was carried out to rehabilitate the closed SKOD describing the conditions and evaluations on the environmental aspects including groundwater quality, surface water quality, ambient air quality, landfill gas and leachate characteristic. From the monitoring process, of particular concern was the high concentration of coliform found in all groundwater samples ranging from 100 to 16000 CFU/100mL. Groundwater quality at NW3 was among the most polluted points. Besides, the surface water quality at the downstream of Sungai Beranang has deteriorated due to the activities carried out at SKOD. The methane gas produced was considered high when the volume of methane gas recorded was 53.4%. Inevitable, there is ample discussion on technical management on upgrading an open dumpsite, but either little or no focus on how this management can be gathered and integrated for easier access. This is because data related to the waste disposal sites are generally lacking in Malaysia. Thus, this research study was carried out by using the Geographic Information System (GIS) which can store and integrate data in facilitating the process of rehabilitation in SKOD. For the rehabilitation of SKOD, relevant data such as geological, groundwater quality, water quality, leachate characteristic, landfill gas and waste composition were gathered and assessed. The collected data was input in a GIS-based inventory. The proposed database can accommodate new information on the landfill by updating the qualities of groundwater, surface water and air. Besides, the database introduced can also accommodate all the data in a comparable manner which can help the stakeholders in making new policy and decision to improve the rehabilitation of SKOD. The outcome of this research would definitely facilitate all the stakeholders and practitioners involving in solid waste management. It can be served as a case study to help in setting up a database in planning and management which is one of the technical capability developments proposed in the National Strategic Plan for Solid Waste Management in Malaysia.